Are fears of an increase in casualization due to Covid-19 justified? - Feyen, Jan (Maskana, 2020)
I am afraid that the answer to this question is YES. The impact of the pandemic on the economy will be tremendous. Just to give a small example, according to the Department of Labor and Employments of the Philippines (June 2020) went exactly 69,022 employees –from more than 2,000 establishments across the country– jobless. Unfortunately, this number does not include the small private businesses that went bankrupt as a consequence of the week-long lockdowns. And the same unfavorable picture holds for many countries. To illustrate the impact on the private sector, the second example is taken from Muskegon city in the U.S. state of Michigan, with a 2020 census population of 36,903, the 30th largest city in Michigan. The city is proud to have the largest beach in West Michigan, a city rich with history, a high level of services, recreational opportunities, and spectacular shoreline, and a low cost of living. However, due to Covid-19 the recreational-based economy collapsed and with the winter just at the corner the need for assistance is increasing rapidly, and at this very moment, the number of Muskegon County residents facing hunger has risen to 20.6%. The job loss that we witnessed so far has largely been temporarily, but permanent job loss is rising.